1958
DOI: 10.1111/j.1749-6632.1958.tb42639.x
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Effects of Five Polyfunctional Alkylating Agents on the Rat Fetus, With Additional Notes on the Chick Embryo

Abstract: Polyfunctional alkylating agents have been studied for evidence of individual specificity of action on normal tissues and on tumors by using biological systems in which effects on multiple factors can be observed simultaneously. In these systems apparently related agents may reveal different patterns of biological activity.The principal system used in the studies to be reported here was the pregnant rat and its fetuses. There are several reports on the normal development of the rat fetus,'-* and many drugs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

1958
1958
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(17 citation statements)
references
References 12 publications
1
14
0
2
Order By: Relevance
“…Intraperitoneal administration of HN2-hydrochloride/g to mice during gestation resulted in serious teratogenic effects (Danforth and Center, 1954). Haskin (1948) and Murphy et al (1958) reported similar findings in rats given HN2-hydrochloride/kg subcutaneously during gestation.…”
Section: Nitrogen Mustardssupporting
confidence: 68%
“…Intraperitoneal administration of HN2-hydrochloride/g to mice during gestation resulted in serious teratogenic effects (Danforth and Center, 1954). Haskin (1948) and Murphy et al (1958) reported similar findings in rats given HN2-hydrochloride/kg subcutaneously during gestation.…”
Section: Nitrogen Mustardssupporting
confidence: 68%
“…Cyclophosphamide is known to have a selective inhibitory effect on the proliferating mesenchyme of developing em bryos [Murphy et al, 1958: Chaube et al, 1967Singh et al, 1971 j and thus interferes with normal chondrogenesis and osteogenesis. In the sequence of events leading to development of a limb, its distal portion, which is rapidly proliferating, lies within a critical period of sensitivity to such inhibition [H askin, 1948].…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that other animal studies have shown that the structurally similar nitrogen mustards are potent teratogens Murphy et al, 1958;Sanyal et al, 1981).…”
Section: Human Studiesmentioning
confidence: 99%